Peaks and Valleys: The Lived Experiences of International Students Within an English Immersion Program Using the Integrated Skills Approach - Stegall, Jennifer (Journal of International Students, 2021)
This qualitative phenomenological study examined how 11 international students experienced learning English within an intensive English immersion program, which used an integrated skills approach for language learning. Participants included seven males and four females from Africa, Asia, Central America, Middle East, and South America.  Drawing on sociocultural and sociolinguistic theories, data analysis suggested that the participants experienced a range of competing emotions and relied on instructors for support and guidance throughout the learning process. In addition, participant testimonies demonstrated that successful language learning occurred when instructors met their social needs (e.g., provided a sense of belonging) and respected their cultural mores (e.g., supported a family-orientation in class). Implications from this study offer insights for university-based immersion programs in the United States.